WO3 as a nucleating agent for BaO/SrO/ZnO/SiO2 glasses – experiments and simulations. Issue 32 (12th July 2018) - Thieme, Christian; Erlebach, Andreas; Patzig, Christian; Thieme, Katrin; Sierka, Marek; Höche, Thomas; Rüssel, Christian
Abstract : In glasses from the BaO–SrO–ZnO–SiO2 system, the addition of up to 4 mol% WO3 leads to volume crystallization. Abstract : Recently, it has been shown that the Ba1− x Sr x Zn2 Si2 O7 crystal phase has a negative coefficient of thermal expansion. However, technological applications of this material as low thermal expansion glass ceramics are limited by the undesired surface crystallization of the corresponding glass. Surface nucleation, however, can be turned into bulk nucleation by adding nucleating agents. Here, glasses in the base system BaO–SrO–ZnO–SiO2 with small additions of ZrO2 and WO3 were synthesized and their crystallization behavior was investigated using thermal analysis, X-ray diffraction, electron microscopy, and density functional theory simulations. The addition of WO3 leads to the formation of volume crystals with a scheelite crystal structure (Ba1− x Sr x WO4 ) in high number density. The limited incorporation of Si 4+ ions into these crystals is discussed. Possible crystal lattice sites for Si 4+ were located by density functional theory simulations. In a much lower number density, crystals with a crystal structure similar to the high-temperature polymorph of BaZn2 Si2 O7 and the Ba1− x Sr x Zn2 Si2 O7 composition crystallize as well. These crystals can reach a larger size than the scheelite crystals that occur in parallel. The overall microstructure is thus formed by small dendritic crystals with a scheelite structure and huge Ba1− x Sr x Zn2 Si2 O7 crystals. Both of them seem to grow independently of each other. In spite of the high anisotropy of both phases, the microstructure is revealed to be free of cracks.